(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
International policies are the product of certain national interests associated with world politics and international conflict. Thus, the theory of regional blocs, and the so-called new regionalism, which constituted one of the important trends in contemporary international relations, and the theories of international conflict, The international conflicts that have resulted in the nature of the current international political order based on a cross-section , or the conflicting interests of regional blocs, including the emerging blocs, to contribute to the development of the current international order. Not only as an extension or expression of regional interests but also as a response to global developments within the framework of the historical shifts and transformations of the world order, without ignoring the influence of the East in international relations throughout history. السياسات الدولية هي نتاج مصالح قومية معينة مرتبطة بالسياسة العالمية, والصراع الدولي, لذلك برزت نظرية التكتلات الإقليمية, وما يطلق عليه الإقليميّة الجديدة التي شكلت إحدى الاتجاهات المهمّة في العلاقات الدولية المعاصرة , وما رافقها من نظريات النزاع الدولي, و التبدلات في صيغ العلاقات الدولية بنتيجة التنافس والنزاعات الدولية التي نتج عنها طبيعة النظام السياسي الدولي الحالي المبني على تقاطع, أو تضارب مصالح التكتلات الاقليمية, ومنها التكتلات الناشئة لتساهم في بلورة النظام الدولي الحالي, كون النظم الإقليمية الجديدة، في عالم اليوم، تختلف عن إقليمية الستينيات من القرن العشرين حيث أنها ليست امتداداً, أو تعبيراً عن مصالح إقليمية فحسب، بل هي استجابة للتطورات العالمية في اطار المنعطفات والتحولات التاريخية للنظام العالمي ، من دون تجاهــل وجود تأثير للشرق في العلاقات الدولية على مر التاريخ.